2009
DOI: 10.1007/s00244-009-9356-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Residual DDTs in Freshwater and Marine Fish Cultivated Around the Pearl River Delta, China

Abstract: Six species of freshwater fish collected from 10 fishponds in Shunde and Zhongshan, China, four species of marine fishes collected from different mariculture farms [four in Hong Kong (Tung Lung Chau, Ma Wan, Cheung Chau and Kat O) and two in mainland China (Daya Bay and Shenzhen)] together with feed (both trash fish and commercial pellets) and sediment were analyzed for DDTs. Total DDTs in freshwater fish flesh decreased in the order of: carnivores [1742 microg/kg lipid weight (l.w.)] > herbivores (165 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…p,p 0 -DDE was the predominant component of DDTs in all samples from the six sampling sites of the northern SCS. This result was consistent with some previous studies (Storelli et al 2008;Leung et al 2010). o,p 0 -DDT was not detected in samples from Xiamen and Sanya, and only few o,p 0 -DDD existed in the muscle of golden threads from Shantou, Yangjiang, Beibu Gulf and Haikou.…”
Section: Composition Profiles Of Pops In Golden Threadssupporting
confidence: 94%
“…p,p 0 -DDE was the predominant component of DDTs in all samples from the six sampling sites of the northern SCS. This result was consistent with some previous studies (Storelli et al 2008;Leung et al 2010). o,p 0 -DDT was not detected in samples from Xiamen and Sanya, and only few o,p 0 -DDD existed in the muscle of golden threads from Shantou, Yangjiang, Beibu Gulf and Haikou.…”
Section: Composition Profiles Of Pops In Golden Threadssupporting
confidence: 94%
“…relative to omnivores (42.5 lg/kg, l.w.) 21 . In the control group, the DDTs concentrations in carp (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mid-range values were observed in medium-sized herbivorous fish species (M. amblycephala). It has been suggested that bottom-dwelling omnivorous species that feed on suspended solids and/or sediments, such as molluscs (C. chinensis) and mud carp (C. carpio), may accumulate greater concentrations of contaminants (Zhou et al, 1998;Zhou and Wong, 2000;Leung et al, 2010;Kwok et al, 2013) and that species that feed on algae and zooplankton, such as P. hyalocranius and shrimp (L. modestus), may accumulate contaminants to a lesser degree (Zhou and Wong, 2000).…”
Section: The Bioaccumulation Of Ocps In Aquatic Biotamentioning
confidence: 99%